KESETARAAN GENDER: Kontestasi Rezim Internasional dan Nilai Lokal - Dzuhayatin, Siti Ruhaini (Sunan Kalijaga State Islamic University & The Asia Foundation, 2012)
Gender equality is a great desire of the world community. Measure of a country's development is the existence of gender justice. This principle is a process that ensures a balance between men and women in access and opportunities, participation in decision-making and control of development benefits. The existence of strong current in the international world coupled with the lack of readiness of the people of Indonesia, where the response is sluggish as evidenced by the birth of KKG bill was cause polemics. There is not a society that can spontaneously accept those values but are not always opposed to these values permanently.